Does annual report readability explain the accrual anomaly?. Issue 3 (28th May 2021) - Liu, Ming; Liu, Zhefeng
Abstract : Purpose: The purpose of the study is to investigate the possible role of annual report readability in accrual anomaly, shedding light on why investors fail to incorporate accruals information in a timely and unbiased manner beyond the original naive investor fixation explanation. Design/methodology/approach: Using five proxies of annual report readability and available data over 1993–2017, we investigate whether accrual overpricing is more severe when annual reports are less readable. Findings: We find little (substantive) evidence of accrual overpricing among high (low) readability firms. The readability effects are contingent on the level of business complexity and earnings management. Research limitations/implications: This study extends the original naive investor fixation explanation and documents annual report complexity as a market friction in explaining the accrual anomaly, contributing to the mispricing vs risk debate and supporting the efficient market hypothesis. Practical implications: Low readability of annual reports is a red flag to investors. Social implications: This study provides support for regulatory initiatives aimed at enhancing readability of corporate disclosures to address market frictions and improve market efficiency. Originality/value: Accrual anomaly has posed a challenge to the efficient market hypothesis. This study draws on and adds to the line of research indicating that annual report complexity is a friction erecting a barrier to transparency, hindering market efficiency. This study contributes to our understanding of the enigmatic accrual anomaly.